The Comparison of Learning Radiographic Extraoral Anatomic Landmarks through Lecture and blended method(Computer-Assisted teaching and Lecture):An interventional Study - T ahmine Razi; Ali r eza Sighari deljavan (Tabriz University of Medical Sciences, 2013)
Introduction: One of the main problems in learning extraoral radiographic anatomic indexes is the long interval between presentation of radiology and human anatomy courses, resulting in forgetting anatomic regions. Therefore, radiographic indexes are formed as complete abstract and transient images in students' minds; as a result, their learning and retention decrease. The aim of this study was to compare lecture with combination of computer-assisted learning and lecture of extra-oral radiographic landmarks among dental students. Methods: This interventional study was carried out in 2009 on 51 dental students of Tabriz University of Medical Sciences. Students were randomly allocated into two groups. The first group was taught through a teaching method which involved lectures in the classroom. In the second group, a CD was given to the students. The teaching was accomplished through presentation using skull. Six months after finishing the teaching, both groups took a similar test for evaluation of long term learning. The data was analyzed by SPSS 16 using U Mann-Whitney test. Results: There was no significant differences in the mean scores between the two groups in the first exam after teaching (P=0.13), yet it was significant in the second exam (regarding retention) (P=0.006), and average of non-traditional teaching method group (20.89±10.23) was higher than that of lecture group (13.48±6.39). Conclusion: Based on the results, non-traditional technique of teaching was not more effective than the lecture in short-term learning but in longterm learning, non-traditional technique was more effective than the lecture.